Microplastic impacts physiological mechanisms of marine, diadromous, and freshwater crustaceans - Leite, Héllen Siqueira [UNESP]; da Costa, Juliana Rodrigues [UNESP]; Calbo, Barbara Bernardes [UNESP]; Capparelli, Mariana; Neves, Claudia [UNESP]; Gimiliani, Giovanna Teixeira; Augusto, Alessandra [UNESP] (Elsevier, 2025)
The effects of microplastic on species inhabiting different saline gradients remain unclear, particularly the impact of glitter particles. We investigated the effects of glitter on the physiological mechanisms of species from various saline environments using the following models: a marine/estuarine shrimp (Penaeus vannamei), a diadromous shrimp (Macrobrachium amazonicum), and an exclusively freshwater shrimp (Macrobrachium potiuna). The animals were exposed to varying glitter concentrations (0, 0.4, 4 and 40 mg.L-1) for 10 days, and to the salinities where they are found in nature. In addition, we evaluated the ability of one of the species (P. vannamei) to recover its physiology and morphology when transferred to glitter-free water after previous exposure to the pollutant for six days. We examined multiple mechanisms, including oxygen consumption, nitrogen excretion, hepatosomatic index, energy substrate oxidation, and osmoregulation. P. vannamei showed 13 % mortality at salinity 30. Physiological parameters exhibited specific variations in response to salinity and/or glitter concentration. Glitter exposure affected oxygen consumption in all three species, but with contrasting responses: P. vannamei exhibited increases up to ∼200 % (depending on salinity), likely due to elevated energy demands, while M. amazonicum and M. potiuna showed reductions up to 70 %, potentially indicating gill damage. In M. amazonicum, glitter exposure enhanced the species' hyperosmotic regulatory capacity. Penaeus vannamei could not recover its hepatosomatic index and gill and intestinal morphologies after being transferred to glitter-free water. We conclude that glitter significantly alters physiological functions related to energy metabolism and osmoregulation. However, since these responses are salinity-dependent, the ability to migrate across different salinity gradients may provide an adaptive advantage for species exhibiting such behavior. The results obtained provide significant insights into the response of shrimps from different saline gradients to microplastics, which is still a major gap in our knowledge.